SAFARI KB PENGGUNAAN IUD DI DESA AROSBAYA BANGKALAN - Merlyna Suryaningsih; Soliha Soliha; Siti Rochimatul Lailiyah (STIKES NGUDIA HUSADA MADURA, 2019)
Family planning is an effort to increase awareness of community participation through maturing age at marriage, regulation, birth, fostering, family resilience and improving family welfare to create a happy and prosperous small family (Yuhedi and Kurniawati, 2013). Based on the results of information obtained from the Arosbaya Health Center, the prevalence of Family Planning (KB) in Bangkalan Regency in 2017 reached 72.97 percent. In 2018 the priority level is 71.99 percent. Meanwhile, from 2019 to April, the prevalence rate is 67.88 numbers. From year to year, community participation in family planning programs tends to decline. It is known that the prevalence is a measure of the level of participation and public awareness. Privalence is the percentage of fertile age couples (PUS) participating in family planning. If the percentage is high, the level of public awareness is also high. However, in Bangkalan, the participation rate is still low. However, the Family Planning Office for Women's Empowerment and Child Protection (KB P3A) in Bangkalan Regency is actively conducting socialization to the community. From the existing problems, we are planning to go on a family planning IUD safari, namely through the installation of a free IUD. The target of family planning counseling and counseling is fertile age couples and community leaders, with a total of approximately 50 people. Meanwhile, the free IUD is intended for women of reproductive age who wish to regulate pregnancy. The highlight of this family planning safari was held for 2 days. The output target to be achieved from this community service is the publication of reputable scientific journals.